Implantação do transplante ortotópico de fígado humano no Estado do Ceará - Garcia, José Huygens Parente (2002)
The orthotopic liver transplantation is the only effective treatment for the end-stage liver diseases. The state of Ceará, with a population of about seven million inhabitants did not offer, until recently, this therapeutic modality. In 1999 an experimental liver transplantation program in pigs was initiated in the University Hospital of the Federal University of Ceará with the objective to group and train a multidisciplinary team in this procedure. On May 17th 2002, all these efforts were rewarded with the successful fulfillment of the first liver transplantation. Since then were realized six liver transplants with inferior caval vein preservation, a technical variant called piggyback. The patients average age was 39.5 years and five of the recipients were men. The etiology of the liver failure was virus C cirrhosis in five patients and Wilson´s disease in one. This patient had a clinical presentation of acute hepatic failure and priority for transplantation. There were an average of 2.6 packed red blood cells per patient, the graft cold ischemia time was in average 7.5 hours and the mean hospitalization time 17 days. All patients were weaned from ventilation until six hours of post transplant. Five patients presented normalization of the hepatic transaminases and bilirrubins as well as the prothrombin time and left the hospital between the 10th and 16th day. One patient had an acute increased in hepatic enzymes, characterizing a primary graft dysfunction, and presented variceal and diffused bleeding, dying at the 8th post operative day. Concluding, there was a 100% technical success, and an initial survival (more than 30 days) of 83,3%. After these successful results, the liver transplant program was consolidated as a therapeutic option in the State of Ceará.